2007
DOI: 10.1080/02699050701796960
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and drug use following traumatic brain injury: A prospective study

Abstract: More active intervention is needed to reduce alcohol and drug use following TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
69
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 26 publications
13
69
0
1
Order By: Relevance
“…There is a highly predictive co-relation between drinking before injury and drinking after injury [14,18,19]. This means a history of alcohol abuse prior to TBI increases the likelihood of alcohol abuse disorders and hazardous drinking post-TBI.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a highly predictive co-relation between drinking before injury and drinking after injury [14,18,19]. This means a history of alcohol abuse prior to TBI increases the likelihood of alcohol abuse disorders and hazardous drinking post-TBI.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…While the majority of studies show a similar increased preference for alcohol by males as compared to females [12,15,19], others show no significant difference between the sexes [14]. In a study by Weil [21], the juvenile mice that were subjected to brain injury showed an increase in alcohol consumption following the injury which was limited to female mice only.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations